The Effect of The Role of Marketing Communications and Primary Service Quality on Customer Satisfaction of Developed HRD on The Account Representative (AR) - Anggit Yoebrilianti Kayubiyanto; Ardy Nugroho (Almana : Jurnal Manajemen dan Bisnis, 2021)
This study takes the title of a study on the effect of marketing communication and excellent service quality on customer satisfaction of customer HRDs at the BPJS Ketenagakerjaan Account Representative (AR) Serang Branch Office. Marketing communication is a communication activity that seeks to combine advertising with other marketing communication tools such as Advertising, Public Relationship, Direct Selling, Promotion, Personal Selling. In addition, factors that can affect customer satisfaction are the quality of service that is owned by the company. The quality of the assessment services includes reliability, responsiveness, assurance, empathy. The purpose of the study was to determine the effect of the Role of Marketing Communications and Primary Service Quality on Customer Satisfaction. This study uses quantitative methods and sampling in this study using purposive sampling method, totaling 150 companies in the Platinum & Gold category from a total population of 574 company HRDs. The results showed that from the results of multiple linear analyses, there was a significant influence between the independent variables of Marketing Communication and Service Quality on the dependent variable, namely Customer Satisfaction of the customer of HRD. From the results of the t-test, it is found that Marketing Communication has a positive and significant effect on customer satisfaction and Service Quality has a positive and significant effect on customer satisfaction.